2014
DOI: 10.1108/jkm-04-2014-0123
|View full text |Cite
|
Sign up to set email alerts
|

Wiki for knowledge sharing, a user-centred evaluation approach: a case study at STMicroelectronics

Abstract: Purpose – The purpose of this paper is to study how a Wiki is used for knowledge sharing within an organization. Design/methodology/approach – The aim of this research is to evaluate this Wiki performance regarding knowledge sharing objectives. Findings – A Wiki has been deployed since several years within STMicroelectronics Company to improve Business Intelligence teamwork. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…These new means of KS have become the attention areas for researchers (Goswami and Agrawal, 2018). Studies were taken to examine and explore KS by means of various ICT tools and technologies such as newsgroups, electronic bulletin boards, emails, chat rooms (Li et al, 2006), wiki (Brichni et al, 2014) and Weblogs (Kaiser et al, 2009;Papadopoulos et al, 2013). Emergence of social media tools in recent times has given new opportunities to researchers to examine these aspects of KS.…”
Section: Resultsmentioning
confidence: 99%
“…These new means of KS have become the attention areas for researchers (Goswami and Agrawal, 2018). Studies were taken to examine and explore KS by means of various ICT tools and technologies such as newsgroups, electronic bulletin boards, emails, chat rooms (Li et al, 2006), wiki (Brichni et al, 2014) and Weblogs (Kaiser et al, 2009;Papadopoulos et al, 2013). Emergence of social media tools in recent times has given new opportunities to researchers to examine these aspects of KS.…”
Section: Resultsmentioning
confidence: 99%
“…At the micro level, it was found that individual motivation, individual capabilities and reflexivity were likely to influence the co-creation of artifacts in collaborative knowledge building. Individual motivation was addressed in the work of Maaninen-Olsson et al (2008), Mueller (2012), Schwabe and Salim (2002), Brichni et al (2014) and Kreiner (2002). Individual motivation (also referred to as “intrinsic motivation”; see, for instance, Mueller, 2012) seemed to be a crucial individual factor enabling proper co-creation and subsequent use of artifacts (Brichni et al , 2014), especially in the long-term in conjunction with individual awareness and willingness to contribute to the creation of artifacts (Brichni et al , 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Individual motivation was addressed in the work of Maaninen-Olsson et al (2008), Mueller (2012), Schwabe and Salim (2002), Brichni et al (2014) and Kreiner (2002). Individual motivation (also referred to as “intrinsic motivation”; see, for instance, Mueller, 2012) seemed to be a crucial individual factor enabling proper co-creation and subsequent use of artifacts (Brichni et al , 2014), especially in the long-term in conjunction with individual awareness and willingness to contribute to the creation of artifacts (Brichni et al , 2014). Individual motivation was found to allow organizational members “to understand each other’s knowledge and work activities” (Maaninen-Olsson et al , 2008, p. 271), with positive effects on knowledge sharing among members and teams (Mueller, 2012) as well as to achieve desired outcomes (Kreiner, 2002; see also Barney, 1986).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among other solutions, STMicroelectronics has opted for the use of a Wiki to capitalize its expert knowledge, called Stiki . In a previous publication [4], an evaluation of Stiki use for knowledge sharing was performed. One of the evaluation findings concerns the importance of pages structuring in Wiki .…”
Section: Introductionmentioning
confidence: 99%